Integrasi Kebijakan Kurikulum Berbasis Pesantren Dalam Mengembangkan Prestasi Akademik dan Non Akademik - Zamroji, Muhammad; Robi’ul Afif Nurul ‘Aini (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2023)
Abstract: This research examines the implementation of the pesantren-based curriculum at MIN 4 Jombang. The purpose of this study was to describe the implementation, evaluation, supporting and inhibiting factors for the implementation of the pesantren-based curriculum at MIN 4 Jombang. The application of the pesantren curriculum at MIN 4 Jombang is carried out using the SMART curriculum which is applied with habits that are carried out every day. This study uses a qualitative approach, while the type of research is a case study, as well as data collection techniques using observation, interviews and documentation which the researchers will later describe in the data analysis including data reduction, data display and drawing conclusions. the research uses several validity checking techniques that researchers examine, including: transferability, confirmability, depandability and confirmability. Research results include: 1). Implementation of a well-structured and effective pesantren-based curriculum using the SMART curriculum which is applied with daily habits. 2). The evaluation is carried out at MIN 4 Jombang by conducting written or oral tests every semester. 3). Factors supporting the implementation of the pesantren-based curriculum include the environment, parental support, the attitude of the teacher who cares. Inhibiting factors include lack of facilities and infrastructure, students with different abilities, lack of support from parents.